(untitled) (Islamic Sciences Journal, 2024)
ABSTRACT Ismail Raji Al-Faruqi is considered one of the most prominent Islamic thinkers in the twentieth century. He was born in 1921 to a family with an academic and social standing in Palestinian society, whose lineage goes back to the second Caliph Omar bin Al-Khattab (may God be pleased with him). He was the first to consider the project of establishing education according to the theory. Islamic education in education and called for rewriting the curricula from the Western style to the Islamic style. The importance of this research is highlighted in that it seeks to shed light on Al-Farouqi’s thought and his efforts in establishing Islamic education in Pakistan, as he sees that Islam is a religion, a state, a belief, work, acts of worship, and transactions. . His vision was based on the process of Islamization of educational curricula in Pakistan, and he addressed the problems surrounding it that hindered its development and prosperity, and looked into ways of its development and progress. The subject of the study is to answer its main question: What is the role of Ismail Raji Al-Farouqi in the field of Islamic education in Pakistan? The study aimed to identify the reality of Islamic education in Pakistan and the role of the Pakistani government in this field. The historical approach was used to find out the most prominent things that happened to Islamic education in Pakistan during the sixties, and the descriptive approach to collect and analyze information related to Islamic education in Pakistan.